2017
DOI: 10.1097/qad.0000000000001363
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of the arginine pathway and its relationship to inflammation in HIV

Abstract: Background Nitric oxide helps maintain vascular function and is generated through the oxidation of arginine. Whether altered arginine metabolism may lead to elevated levels of inflammation in HIV is unclear. Methods We performed a cross-sectional analysis of HIV-infected adults on stable ART with HIV-1 RNA < 50 copies/mL and HIV-uninfected controls. We measured biomarkers in the arginine pathway, markers of systemic inflammation, and monocyte activation. T-tests, chi-square tests and propensity score matchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Not all patients achieved "crisis resolution" based on the set definition of a pain score <4, which is a common challenge with this outcome measure. In addition to SCA, some patients may have been impacted by their nutritional status or the presence of infectious diseases like malaria or HIV, all conditions that impact global arginine bioavailability, 19,[37][38][39][40][41][42][43] and potential response to arginine therapy. Finally, the specific mechanism(s)-of-action for arginine therapy remains to be determined, although several feasible mechanisms that include NO generation, 23 improvement in mitochondrial function/bioenergetics, 31 and decreased oxidative stress 22,44 have been described, in addition to NO-independent mechanisms specifically targeting pain pathways that impact kyotorphin production.…”
Section: Discussionmentioning
confidence: 99%
“…Not all patients achieved "crisis resolution" based on the set definition of a pain score <4, which is a common challenge with this outcome measure. In addition to SCA, some patients may have been impacted by their nutritional status or the presence of infectious diseases like malaria or HIV, all conditions that impact global arginine bioavailability, 19,[37][38][39][40][41][42][43] and potential response to arginine therapy. Finally, the specific mechanism(s)-of-action for arginine therapy remains to be determined, although several feasible mechanisms that include NO generation, 23 improvement in mitochondrial function/bioenergetics, 31 and decreased oxidative stress 22,44 have been described, in addition to NO-independent mechanisms specifically targeting pain pathways that impact kyotorphin production.…”
Section: Discussionmentioning
confidence: 99%
“…In our current studies we demonstrate that SIK3 plays a direct role in mediating this inflammatory insult. Arginine pathway is considered a major modal point for production of nitric oxide and reactive nitrogen species [ 44 ]. We have shown that the pro-inflammatory enzymes iNOS and ASS-1 are upregulation through SIK3 mediated inflammatory events resulting from high salt stimulation while anti-inflammatory Arg-1 and ODC are downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency may be due to the fact that the PLHIV in our cohort had a longer duration of ART intake (median years = 6.4) compared to previous studies, which is supported by earlier evidence that ART can partially restore the gut microbial composition 10 . Functionally, PLHIV in our study showed increased microbial capacity of L-tryptophan biosynthesis and decreased de novo biosynthesis of ornithine from 2-oxoglutarate, functions that have been related to inflammation and vascular function 29,32 , respectively. This observation supports the idea that those functional changes in the gut microbiome in PLHIV using ART contribute to the persistent inflammation seen in these individuals.…”
Section: Discussionmentioning
confidence: 61%
“…At metabolic pathway–level, we observed differential abundances in several amino acid biosynthesis pathways, including enriched L-tryptophan biosynthesis (PWY-6629) and depleted L-ornithine and L-citrulline biosynthesis pathways (ARGININE-SYN4-PWY, CITRULBIO-PWY) in PLHIV (Supplementary Table 3). Importantly, tryptophan and citrulline both play critical roles in inflammation 29,30 , while ornithine can later be turned into Nitric Oxide (NO), which is important for vascular function 31,32 . In addition, the reductive tricarboxylic acid (TCA) cycle I (P23-PWY) was enriched in PLHIV.…”
Section: Resultsmentioning
confidence: 99%